PENGARUH PENERAPAN PEMBELAJARAN ANALOGI TERHADAP HASIL BELAJAR SISWA PADA MATERI LISTRIK DINAMIS DI SMP - Radiannur, Radiannur; Sahala, Stepanus; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to known influence of analogy learning toward students’ achievement. Pre-test-posttest control group design was used in this research. Sample of this research was choosen by intact group technique that consisted 18 students’ of IX A grade and 18 students’ of IX B grade. Objective test which consisted 20 Multiple choice test each pretest-posttest used to known student achievement scors. Based on the result of data analysis, found that the average of posttest experiment class was 67,22% and control class was 57,50%. The result of independent t-test analysis using SPSS for Windows 22.0 was 0.00 less than significant value (0.05), it is mean there was significant difference toward student achievement between experiment class and control class. Based on the findings above, it is expected that analogy learning can be used as an alternative remediation activities to increase sudents’ achievement. Keyword : Analogy, Inluence, Student Achievement, Dynamic Electricity